2017
DOI: 10.1504/ijmed.2017.082538
|View full text |Cite
|
Sign up to set email alerts
|

Internationalisation of publicly traded family firms: a transaction cost theory perspective and longitudinal analysis

Abstract: There has been a prominent stream of research investigating internationalisation of organisations. While the importance of transaction costs in the governance decisions of firms has been well established in the literature, transaction cost theory (TCT) in family firms remains underutilised. We examine the impact of family governance (i.e. family ownership and involvement in management and the board of directors) on internationalisation within the domain of TCT using 386 S&P 500 firms. Our findings indicate an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Finally, in three other studies, researchers have found an inverted U-shape forming between family ownership and export intensity (Sciascia et al. , 2012; Memili et al. , 2017; Mitter et al.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 84%
See 1 more Smart Citation
“…Finally, in three other studies, researchers have found an inverted U-shape forming between family ownership and export intensity (Sciascia et al. , 2012; Memili et al. , 2017; Mitter et al.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 84%
“…Finally, in three other studies, researchers have found an inverted U-shape forming between family ownership and export intensity (Sciascia et al, 2012;Memili et al, 2017;Mitter et al, 2012), recognising that family involvement may have positive effects up to a certain level of family ownership and then negative effects afterwards.…”
Section: Introductionmentioning
confidence: 89%
“…Recently the transaction cost theory has been also applied family firms (Memili, Misra, Chrisman, & Welsh, 2017;Verbeke, Yuan, & Kano, 2019), providing interesting explanations on family-specific assets, that can be in turn used to explain entry modes. While the general theory on entry mode has sometimes failed to find an adequate proxy for asset specificity according to transaction cost theory, transaction cost theorists in family business literature agree that family firms are able to develop specific assets, completely different from those of non-family firms.…”
Section: Entry Mode and Family Firms: The Theoretical Approachesmentioning
confidence: 99%
“…Family firms' behaviours are thus affected by these specific family assets and might be explained through the transaction cost lens. Recent studies applying transaction cost theory to family businesses in general (Kano & Verbeke, 2018;Memili et al, 2017;Verbeke et al, 2019) and family firms' entry modes more specifically show that this stream of literature deserves more attention and further research.…”
Section: Entry Mode and Family Firms: The Theoretical Approachesmentioning
confidence: 99%